Discalculia e formação continuada de professores : suas implicações no ensino e aprendizagem de matemática - Thiele, Ana Lúcia Purper (2017)
This research presents a study about dyscalculia and the mode that it has been perceived by teachers who teach mathematics. It aims to analyze how a continuing education offered to teachers who teach Mathematics in Basic Education can modify their perceptions about dyscalculia and the mode that this impacts on their pedagogical practice. For this, sought to achieve some specific objectives: Identify, if they exist, the previous perceptions of the teachers participating in this research about dyscalculia; To verify what are the possible changes of these perceptions at the end of the continued formation about dyscalculia and to analyze how the continued formation repercussion in their pedagogical practices. To construe the theoretical framework, the study was based on some axes: neurosciences; learning difficulties; dyscalculia. The neuroscience is based mainly on the ideas of authors such as: Consenza and Guerra (2011); Ciasca (2006); Izquierdo (2002); Spitzer (2007); Haase (2010). To base the learning disabilities, mainly uses studies of: Ciasca (2006); Rotta (2006); Bridi Filho and Bridi (2016); Riesgo and Olweiller (2006). And, to address the dyscalculia, the researches of Kocs (1974); Haase (2010); Rotta (2006); Dehaene (2006); Consenza and Guerra (2011) were used. Twenty-three teachers who teach mathematics in Basic Education participated in this research. The teachers performed a continuing education about learning difficulties and dyscalculia and answered two questionnaires, one before and one after training. To analyze the data coming from the answers given to the questionnaires was inspired by for the Discursive Textual Analysis method (MORAES; GALIAZZI; 2011). Through the analysis, it shows that before the training the teachers attributed various denominations and characteristics to the dyscalculia, not having a clear differentiation in relation to the transtorn and the learning difficulties. This unfamiliarity gave rise to twelve categories about the definition of learning difficulties and ten categories about dyscalculia. After the continuing education these categories decreased to three and two, respectively, evidencing the need that these teachers have to obtain theoretical and practical subsidies on this theme. It is possible to show that the answers given to the post-questionnaire converged to a more precise definition of dyscalculia, denominating it as a transtorn or disorder. In addition, teachers listed more accurately the characteristics of dyscalculia and their differences in relation to learning difficulties. It verifies that teachers are not always prepared to deal with the transtorn and not even recognize signs that indicate evidence of a student with dyscalculia, besides not knowing possible interventions that can help you in the classroom. In this way, it points the need for a continuing education that account for the deepening about difficulties and disorders of learning in Mathematics for teachers who teach Mathematics at any level of Basic Education.